Osteocalcin as a Predictor of Body Composition in Healthy Adults. (29th May 2020) - DeLuccia, Rosemary; Cheung, May; Altasan, Asma; Al-Ani, Sumer; Parekh, Rushali; Sukumar, Deeptha
Abstract: Objectives: The objectives of this study were to determine if body composition and nutrient status are dependent on serumosteocalcin concentrations in healthy adults. Methods: Adults 20 to 70 years of age completed fasting blood sampling to measure serum ionized calcium concentrations, serum ionized magnesium concentrations, and serum total osteocalcin concentrations. Dual Energy X-Ray Absorptiometry was also completed to measure body composition variables including body mass index (BMI), total fat mass, total fat freemass, total lean mass, android fat, gynoid fat, trunk fat, and visceral adipose tissue. Results: A sample of 60 women and 78 men with a median age of 33.0 (21.0) years were categorized into two groups accordingto the median osteocalcin concentration measured: low osteocalcin (12.11 ± 2.72 ng/mL), and high osteocalcin (26.80 ± 9.72 ng/mL). Means, standard deviations, medians and interquartile ranges were calculated and independent t-tests, and Mann Whitney U tests were conducted to determine differences between groups in body composition variables. Total fat mass, total fat percentage, android fat, trunk fat, and trunk fat percentage were all significantly higher, and totalfat free mass, fat free mass percentage, total lean mass, lean mass percentage, serum ionized calcium concentrations, and serum ionized magnesium concentrations were all significantly lower ( P  < 0.05) in the low osteocalcin groupcompared to the high osteocalcin group. There were no differences ( P  >0.05) between groups in weight, gynoid fat, visceral adiposity tissue, or visceral adiposity tissue percentage. Conclusions: The results of this study provide preliminary evidence that serum osteocalcin concentrations can predict bodycomposition. Interventional studies should consider methods to alter osteocalcin concentrations through vitamin ormineral supplementation as a means to improve body composition in adults. Funding Sources: American Heart Association; Drexel University.